Transcranial current stimulation in epilepsy: A systematic review of the fundamental and clinical aspects - Simula, Sara; Daoud, Maëva; Ruffini, Giulio; Biagi, Maria Chiara; Bénar, Christian-G.; Benquet, Pascal; Wendling, Fabrice; Bartolomei, Fabrice (Frontiers in Neuroscience, 2022)
Purpose: Transcranial current stimulation (tCS) has been proposed as non-invasive therapy for pharmacoresistant epilepsy. This technique involves the application of a weak current across the cortex to change cortical excitability. Although clinical trials have demonstrated the therapeutic efficacy of tCS, its specific effects on epileptic brain activity are poorly understood. We sought to summarize the clinical and fundamental effects underlying the application of tCS in epilepsy. Methods: A systematic review was performed in accordance with the PRISMA guidelines. A database search was performed in PUBMED, MEDLINE, Web of Science and Cochrane CENTRAL for articles corresponding to the keywords “epilepsy AND (transcranial current stimulation OR transcranial electrical stimulation)”. Results: A total of 56 studies were included in this review. Through these records, we show that transcranial direct (tDCS) and alternate (tACS) current stimulation in epileptic patients are safe and clinically relevant techniques for epilepsy. Recent articles reported changes of functional connectivity in epileptic patients after tDCS. We argue that tDCS may act by affecting brain networks, rather than simply modifying local activity in the targeted area. To explain the mechanisms of tCS, various cellular effects have been identified. Among them, reduced cell loss, mossy fiber sprouting, and hippocampal BDNF protein levels. Brain modeling and human studies highlight the influence of individual brain anatomy and physiology on the electric field distribution. Computational models may optimize the stimulation parameters and bring new therapeutic perspectives. Conclusion: Both tDCS and tACS are promising techniques for epilepsy patients. Although the clinical effects of tDCS have been repeatedly assessed, only one clinical trial has involved a consistent number of epileptic patients and little knowledge is present about the clinical outcome of tACS. To fill this gap, multicenter studies on tCS in epileptic patients are needed, involving novel methods such as personalized stimulation protocols based on computational modeling. Furthermore, there is a need for more in vivo studies replicating the tCS parameters applied in patients. Finally, there is a lack of clinical studies investigating changes in intracranial epileptiform discharges during tCS application, which could clarify the nature of tCS-related local and network dynamics in epilepsy.